2005
DOI: 10.1007/s11211-005-7368-1
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Effects of Justice Sensitivity Perspectives on Prosocial and Antisocial Behavior

Abstract: Three studies explore the effects of perspective-specific justice sensitivity on indicators of both prosocial behavior (i.e., existential guilt, solidarity, and responsibility ascriptions towards the disadvantaged) and antisocial behavior (i.e., the willingness to transgress a norm in a moral temptation dilemma). On the basis of theoretical considerations and earlier findings it is expected that being sensitive towards injustice from a beneficiary's perspective is associated positively with prosocial and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
144
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(168 citation statements)
references
References 54 publications
13
144
3
1
Order By: Relevance
“…Indeed, we found positive correlations between relatedness and being sensitive to injustice from a beneficiary's perspective (which is, in turn, correlated with more prosocial behavior, cf. Fetchenhauer & Huang, 2004;Gollwitzer et al, 2005), as well as social responsibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we found positive correlations between relatedness and being sensitive to injustice from a beneficiary's perspective (which is, in turn, correlated with more prosocial behavior, cf. Fetchenhauer & Huang, 2004;Gollwitzer et al, 2005), as well as social responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…More concretely, interdependence should be positively correlated with justice sensitivity, both from a neutral observer's perspective and from a potential beneficiary's perspective (cf. Gollwitzer, Schmitt, Schalke, Maes, & Baer, 2005;Schmitt, Gollwitzer, Maes, & Arbach, 2005). Furthermore, an interdependent self-construal should be related to greater social responsibility (Berkowitz & Daniels, 1963).…”
Section: The Present Studiesmentioning
confidence: 99%
“…This research shows that people who were sensitive as victims may be more egocentric than people who were sensitive as beneficiaries, with the former more concerned about principles of justice and equity only when they were victims of an injustice, and the latter more altruistic and concerned about equity and justice independently of their participation in the situation. These asymmetrical effects were confirmed by Gollwitzer, Schmitt, Schalke, Maes, and Baer (2005), who investigated the effects of the injustice sensitivity dimensions on the adoption of prosocial or antisocial behaviours when facing a moral dilemma. The results demonstrated that whereas the victim dimension was related to the adoption of antisocial behaviours, the beneficiary dimension was related to the adoption of prosocial behaviours.…”
Section: Sensitivity To Injustice: a Factor Of Influencementioning
confidence: 85%
“…The results of Goutas et al (2003), Salhani et al (2005) and Faccenda et al (2005) led us to expect that facing an injustice would predict the adoption of a lower level of moral functioning. Based on the research of associates (1996, 2005), Mohiyeddini and Schmitt (1997) and Gollwitzer et al (2005), sensitivity to injustice was also expected to be a significant predictor of players' moral functioning. However, previous research suggests that the dimensions of sensitivity to injustice need to be distinguished.…”
Section: Sensitivity To Injustice: a Factor Of Influencementioning
confidence: 99%
“…Institutions can only be successful if the latter is true, and psychology can contribute with research and know-how. This research is closely related to psychological research about justice and justice sensitivity (like, for instance, Gollwitzer, Schmitt, Schalke, Maes, & Baer, 2005).…”
Section: Institutional Ergonomics: Creating Citizen-friendly Institutmentioning
confidence: 98%